A study on patent protection and access to affordable drugs /Adelia Adnan…[et al.] - Adnan, Adelia; Zulkifli, Amira Haziqah; Abd Razak, Farah Saira; Zulkifli, Zuliana (2011)
This project paper discusses on patent protection and access to affordable drugs. Chapter one of the project paper presents a background about the laws and issues involved in patent protection and access to affordable drugs. Chapter two of the project paper discusses on the relevant TRIPS provision, the flexibilities of the TRIPS Agreement and the Doha Paragraph 6 System. The flexibilities of the TRIPS Agreement include compulsory license, government use, parallel importation and permitted limited exceptions. Chapter three of the project paper discusses on the implementation of the TRIPS Agreement in various countries, which includes the United States, India, Brazil, South Africa and Malaysia. Chapter four explains the further barriers of the implementation of the TRIPS Agreement. The final chapter discusses the possible alternatives in enhancing access to affordable drugs.